CALCULATION OF AREAS OF IRREGULAR SURFACES IMPLEMENTING THE SOFTWARE AUTOCAD AND MATLAB - Raffo Lecca, Eduardo (2007)
This article raises determine the area of an irregular surface, where is known a set of coordinates of the perimeter of the area. The surface area was determined applying numerical integration and computer aided desing methods, the software to be used for the calculations are: Matlab® and AutoCAD® respectively. The segment cubic interpolation method or splines is the most close to the perimeter boundary of the irregular surface because binds a set of points by splines. The accuracy of calculating the surface area depends on the number of points and the method to use. When the curve is defined perimeter, the application of methods in the calculation of CAD areas of irregular surface is direct, and result is reliable.